2016
DOI: 10.4338/aci-2016-03-r-0042
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Applications of Smart Watches

Abstract: Smart watches are unobtrusive and easy to wear. While smart watch technology supplied with biosensors has potential to be useful in a variety of healthcare applications, rigorous research with their use in clinical settings is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 35 publications
0
52
0
2
Order By: Relevance
“…Wu et al (2012) observe that the healthcare industry employs various mobile communication technologies, including mobile phones, smartphones and hands-free devices. Since 2013, smartwatches have been increasingly used in healthcare applications (Lu, Fu, Ma, Fang, & Turner, 2016). The primary use of these devices has been to continuously track and collect biometric data, including heart rate, number of steps, distance walked and calories consumed (Stegemann, 2015;Varga, Bokor, & Takács, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2012) observe that the healthcare industry employs various mobile communication technologies, including mobile phones, smartphones and hands-free devices. Since 2013, smartwatches have been increasingly used in healthcare applications (Lu, Fu, Ma, Fang, & Turner, 2016). The primary use of these devices has been to continuously track and collect biometric data, including heart rate, number of steps, distance walked and calories consumed (Stegemann, 2015;Varga, Bokor, & Takács, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our models can eventually be used within eHealth applications that do not require wearing a sensor during sleep. This is of special interest for the development of smart watch health apps [33], as they might require frequent battery charging.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that these consumer-grade devices can sometimes have similar precision to clinical-grade actigraphy sensors [31]. There are successful examples of the integration of physical activity wearable data into eHealth tailored applications [32], including smart-watch health applications [33] that can collect physical activity and sleep data directly from the watch.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are attracted toward such devices for example, alarming device, pill count device etc. 2,[20][21][22] Availability of automated devices have simplified the procedure with improved medication adherence devices which are more advanced. With the advent of smart devices, adherence practices have improved a lot.…”
Section: Use Of Colored Codes To Identify Pillsmentioning
confidence: 99%